Pengaruh Penggunaan Bahan Ajar Kalkulus Diferensial Berbasis Pendekatan Open Ended terhadap Kemampuan Representasi Matematis Mahasiswa - Eka Kasah Gordah; Syarifah Fadillah (Jurnal Pendidikan dan Kebudayaan, 2014)
The aim of this research was to investigate the improvement of student’s ability on mathematical representation by using teaching materials based on open ended approach in differential calculus subject. This research was conducted at STKIP PGRI Pontianak in the even semester of 2012/2013 academic year. This research used cluster random sampling by choosing one of the four classes at the mathematics education department in the academic year of 2012/2013. The experimental method with the one group pretest-posttest design was applied in this research. The result of this research showed that: 1) there was an improvement on student’s ability on mathematical representation by using differential calculus teaching material based on open ended approach with moderate of quality of improvement level, 2) there was a difference on student’s ability on mathematical representation when it was viewed from the level of student’s prior knowledge, and 3) there was no difference on student’s ability on mathematical representation when it was viewed from their gender.ABSTRAK Tujuan penelitian ini adalah untuk membandingkan peningkatan kemampuan representasi matematis mahasiswa melalui penggunaan bahan ajar berbasis pendekatan open ended pada mata kuliah kalkulus diferensial. Penelitian dilaksanakan di STKIP PGRI Pontianak pada semester genap tahun akademik 2012/2013. Pengambilan sampel penelitian menggunakan teknik cluster sampling dengan memilih satu kelas dari empat kelas yang ada pada program studi pendidikan matematika angkatan 2012/2013. Penelitian ini menggunakan metode eksperimen dengan desain penelitian the one group pretest-posttest design. Hasil penelitian menunjukkan bahwa: 1) terdapat peningkatan kemampuan representasi matematis mahasiswa melalui penggunaaan bahan ajar kalkulus diferensial berbasis pendekatan open ended dengan kualitas peningkatan tergolong sedang, 2) terdapat perbedaan peningkatan kemampuan representasi matematis mahasiswa jika ditinjau dari tingkat kemampuan awal mahasiswa, dan 3) tidak terdapat perbedaan peningkatan kemampuan representasi matematis mahasiswa jika ditinjau dari gender.